Communicative activism and political impasse: the changing media system in the context of fake news and populism. Issue 4 (27th November 2018) - Splendore, Sergio
ABSTRACT: The absence of an electoral law able to provide a clear winner at the 2013 parliamentary elections has contributed to the 2017 Italian political communication environment. The parties and leaders' communication activities could not find any clear possibility of governing. Nevertheless, the multiplication of available channels has increased the amount of political information available. This article summarizes the communication dynamics within the hybrid media system among political actors, media actors and citizens. It focuses particularly on three different issues: 1) the debates about the obligatory nature of vaccinations; 2) the discussion about the so-called ius soli law; and finally 3) fake news. These issues highlight how political debate in Italy has become highly polarized and characterized by distrust toward traditional newsmakers.